Ciliate SSU-rDNA reference alignments and trees for phylogenetic placements of metabarcoding data - Ľubomír Rajter (Pensoft Publishers, 2021)
Although ciliates are one of the most dominant microbial eukaryotic groups in many environments, there is a lack of updated global ciliate alignments and reference trees that can be used for phylogenetic placement methods to analyze environmental metabarcoding data. Here we fill this gap by providing reference alignments and trees for those ciliates taxa with available SSU-rDNA sequences derived from identified species. Each alignment contains 478 ciliate and six outgroup taxa, and they were made using different masking strategies for alignment positions (unmasked, masked and masked except the hypervariable V4 region). We constrained the monophyly of the major ciliate groups based on the recently updated classification of protists and based on phylogenomic data. Taxa of uncertain phylogenetic position were kept unconstrained, except for Mesodinium species that we constrained to form a clade with the Litostomatea. These ciliate reference alignments and trees can be used to perform taxonomic assignments of metabarcoding data, discover novel ciliate clades, estimate species richness, and overlay measured ecological parameters onto the phylogenetic placements.